2006
DOI: 10.1097/01.rlu.0000222678.95218.42
|View full text |Cite
|
Sign up to set email alerts
|

F-18 FDG Whole-Body PET for the Assessment of Disease Activity in Patients With Rheumatoid Arthritis

Abstract: Visual assessment of FDG uptake shows a significant correlation with clinical evaluation of disease activity in patients with RA undergoing antiinflammatory treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
67
3
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(81 citation statements)
references
References 16 publications
9
67
3
2
Order By: Relevance
“…To our knowledge, this is the first PET study in RA patients showing the potential of 18 F-FDG PET for predicting the response to infliximab therapy early in the course of treatment. Previous 18 F-FDG PET studies visualized the treatment effects of infliximab in RA patients but did not investigate the predictive value of 18 F-FDG PET for clinical response (4)(5)(6)8,9,20). In addition, various other markers have been tested, but-in line with our results-no single marker has consistently been shown to be a predictor of response to infliximab (3-6).…”
Section: Discussionsupporting
confidence: 68%
“…To our knowledge, this is the first PET study in RA patients showing the potential of 18 F-FDG PET for predicting the response to infliximab therapy early in the course of treatment. Previous 18 F-FDG PET studies visualized the treatment effects of infliximab in RA patients but did not investigate the predictive value of 18 F-FDG PET for clinical response (4)(5)(6)8,9,20). In addition, various other markers have been tested, but-in line with our results-no single marker has consistently been shown to be a predictor of response to infliximab (3-6).…”
Section: Discussionsupporting
confidence: 68%
“…FDG-PET in rheumatoid arthritis and seronegative spondyloarthropathy with RA using a visual evaluation score, and concluded that FDG uptake was significantly correlated with clinical evaluations of disease activity in patients with RA before and after treatment with infliximab. Our findings are in agreement with those of Kubota et al [7] and Goerres et al [6] who also recommend the use of a FDG uptake scoring system as a useful tool in the assessment of joint inflammation. The difference between the results of Elzinga et al [14] and the other studies could be due to the use of different treatment modalities (biological vs cytoreductive) and duration of the RE scan.…”
supporting
confidence: 83%
“…The usefulness of PET using FDG-PET to assess synovial inflammation, has been evaluated by a few investigators [3][4][5][6][7] , especially in the setting of RA. Most of these studies produced promising results and were able to quantify inflammation in the joints.…”
Section: Introductionmentioning
confidence: 99%
“…They found a significant correlation between joint count, C-reactive protein (CRP), erythrocyte sedimentation rate (ESR), and affected joints on ultrasound, and positive joints on PET. Similarly, Goerres et al (2) Tc-glucosamine can be locally produced by a nuclear scientist in a major nuclear medicine department and administered to a patient, as one would for a bone scan, and it is easy to produce, cheap to administer, and accessible. Other similar analogs of glucosamine, such as N-[2,4,5-trihydroxy-6-(hydroxymethyl) tetrahydro-2H-pyran-3-yl] acrylamide, have been demonstrated to have anti-arthritic and immunomodulatory effects in adjuvant-induced arthritis but are yet to be tested in humans as imaging agents (9).…”
Section: Discussionmentioning
confidence: 99%